Analysis of Building Envelope Insulation Performance Utilizing Integrated Temperature and Humidity Sensors - Shih-Wei Chen; Cheng-Jui Hsu; Chih-Yuan Chang; San-Shan Hung (Sensors, 2012)
A major cause of high energy consumption for air conditioning in indoor spaces is the thermal storage characteristics of a building’s envelope concrete material; therefore, the physiological signals (temperature and humidity) within concrete structures are an important reference for building energy management. The current approach to measuring temperature and humidity within concrete structures (i.e., thermocouples and fiber optics) is limited by problems of wiring requirements, discontinuous monitoring, and high costs. This study uses radio frequency integrated circuits (RFIC) combined with temperature and humidity sensors (T/H sensors) for the design of a smart temperature and humidity information material (STHIM) that automatically, regularly, and continuously converts temperature and humidity signals within concrete and transmits them by radio frequency (RF) to the Building Physiology Information System (BPIS). This provides a new approach to measurement that incorporates direct measurement, wireless communication, and real-time continuous monitoring to assist building designers and users in making energy management decisions and judgments.